ОСОБЕННОСТИ МОТИВАЦИИ ОБУЧЕНИЯ ИНОСТРАННЫМ ЯЗЫКАМ (World Science, 2020)
The problems and the specifics of motivation during foreign languages teaching in higher educational establishments have been considered in the article. The importance of this problem solving is determined by the fact that educational motivation is a decisive factor of educational process efficiency. Motivation provides interest to learning activity, improves the work of all cognitive mechanisms and speech activity: memory, thinking, attention and also activates the linguistic unit memorization, which stimulates successful foreign language communication. The aim of our investigation is to analyse the nature, structure and approaches of the motivation formation, development and maintenance during foreign languages studying. The object of our investigation is the educational activity motivation, in particular foreign languages teaching. The subject of our investigation is the structure, components, mechanisms of effective functioning, conditions of motivational studying activity development. Different classifications of motivational factors have been considered and the main types of motives during a foreign language studying have been distinguished. The anti-motivation factors which affect the quality of the educational process have been also considered in the context of this work. As a result of investigation, it has been stated that the level of motivation increasing during a foreign language studying is possible only with the complex usage of these conditions.